Antoine Vergote, Founder of the Empirical and Psychoanalytical Approach in the Psychology of Religion - Tomcsányi, Teodóra (European Journal of Mental Health, 2010)
The monograph introduces the reader to the psychology of religion through the work of Antoine Vergote, a theoretician who has influenced the development of this discipline in Europe in fundamental ways for several decades. Behind the iron curtain, the importance of a psychology of religion was suppressed and its cultivation banished from the scope of research. On the solid basis of his life’s work and of his psychoanalytically oriented pioneering research, Vergote now presents the Hungarian reader with empirical methods of studying various cases, his preliminary considerations, and the results of his investigations supported by his insight into several disciplines. Vergote approaches definitions, symbols, and rituals from a wide theoretical foundation making use of different fields such as psychology, theology, and a religiously based and practically oriented pedagogy. While the author has developed a system of criteria to distinguish between healthy and pathological forms of religious practices, he points out that the adequate training of the practitioner is key to a successful treatment. Vergote’s works are now an indispensable resource for any research in the field connecting psychology and theology.